A visita domiciliária na Estratégia de Saúde da Família de um município do interior paulista: os desafios para a equipe de enfermagem - Lopes, Fabiana Alvares (2018)
The present study had as objective to analyze the performance of the nursing team and organization of the home visits (HVs) of the family health units in the interior municipality of São Paulo. It identified the facilities, difficulties, and limitations of these professionals. This was an exploratory and descriptive study, with a qualitative approach, with a sample involving 5 nurses and 10 nursing assistants. The results allowed to list and divide in two thematic units: The non-scheduled HV and the scheduled RV. In the scheduled RV unit, three subcategories have been identified: a) RV for individuals or families with risk/vulnerability evidenced a curative model; b) RV with a family bond, allowing a broad reflection of the process of being born and dying in the community; c) RV care as work process and strengthening of care production. Difficulties and limitations such as overloading of tasks, disorganization of these professionals with excessive internal activities and incomplete teams, unprepared management, professional devaluation, the difficulty of understanding and non-adherence of users to care, difficult access to the home and physical and moral violence were identified.